Kesalahan Berbahasa Sunda pada Siswa Dwibahasawan di SLTP Taruna Bakti Bandung - . Juanda (Humaniora, 2010)
The aim of this research is to investigate written Sundanese errors made by pupils of SLTP Taruna Bakti Bandung. The results show that four types of errors were detected: phonological, morphological, syntactic, and lexical. The phonological errors are close related to such phonemes as /a/ and /u/, /d/ and /y/, /d/ and /r/, /e/, and /a/, /o/ and /u/. The morphological errors include types of lexical errors include the use of loan words or borrowing sich as antusias, bakar, cermin, dalam, gorok, hilang, jatuh, kupas, lestari, madu, pecah, runcing, serius, tinggi, untuk, and wajah.